The Balanced Scorecard for Higher Education — the Case of Maria Curie-Skłodowska University - Świerk, Joanna; Mulawa, Magdalena (Regional Barometer. Analyses & Prognoses, 2015)
The Balanced Scorecard originated by Kaplan and Norton translates strategy into tangible and measurable objectives in four perspectives: financial, customer, internal business process, learning and growth. These perspectives can be modified, extended and adapted to the specific characteristics of company. This popular and modern management tool is used to clarify strategy, vision, and mission. It enables executives to realize their strategy in the most effective way. In contemporary times, the Balanced Scorecard is gaining popularity and has an ever increasing number of applications in the areas of benchmarking, budgeting, Total Quality Management or cost management. Nowadays it is more and more often implemented in the management of universities. The article presents the example of developing the Balanced Scorecard model at Maria Curie-Skłodowska University in Lublin.